Optimal investment by large consumers in an electricity market with generator market power - Pranjal Pragya Verma; Mohammad Reza Hesamzadeh; Steffen Rebennack; Derek Bunn; K. Shanti Swarup; Dipti Srinivasan (Computational Management Science, 2024)
Abstract The investment decisions of energy-intensive consumers can alter the balance of supply and demand in an electricity market. In particular, they can increase the market power of incumbent generators such that prices may increase as a consequence of their investments. Whilst it is therefore intuitive that such investors will wish to consider their effects on the market, it is a challenging problem analytically and one that has been under-researched. In general, the problem can be manifest in any supply chain where demand-side investments influence endogenous price formation in the intermediate product markets. Theoretically, we show how the presence of producer market power decreases demand-side investments and then, computationally we formulate a quad-level program to model the operational implications for a demand-side investor in more detail. With an innovative reduction in complexity to a bilevel model, an efficient solution algorithm for the optimal investment by a demand-side investor is facilitated. We demonstrate computability on a small scale electricity system and the results confirm the theory.
Keywords: 330; Electricity market; Demand investment; Bayesian Nash equilibrium